The long ride home - Travis, Randy; Roberts, Eric, 1956-; Borgnine, Ernest, 1915-; Taylor, Vaughn; Marcarelli, Rob. ([United States] : Lions Gate Home Entertainment, 2003)
"Jack Fowler (Randy Travis) was mistaken for a cold- blooded killer. Now he must find the real murderer before a blood-thirsty posse hangs hom for a crime he didn't commit. Set in the old West in the late 1860s..."-- Container.
English track: Dolby digital 2.0 stereo.
Special features: director's commentary; behind-the-scenes footage.
Randy Travis, Eric Roberts, Ernest Borgnine, Vaughn Taylor.
PG-13.
DVD.
In English with English and Spanish subtitles.
Keywords: Western films